Si-Based Hydrogen-Producing Nanoagent Protects Fetuses From Miscarriage Caused by Mother-to-Child Transmission - Usui, Noriyoshi; Togawa, Shogo; Sumi, Takuya; Kobayashi, Yuki; Koyama, Yoshihisa; Nakamura, Yukiko; Kondo, Makoto; Shinoda, Koh; Kobayashi, Hikaru; Shimada, Shoichi (Frontiers in Medical Technology, 2021)
Mother-to-child transmission of viruses and bacteria increases the risk of miscarriage and various diseases in children. Such transmissions can result in infections and diseases in infants or in the induction of an inflammatory immune response through the placenta. Recently, we developed a silicon (Si)-based hydrogen-producing nanoagent (Si-based agent) that continuously and effectively produces hydrogen in the body. Since medical hydrogen has antioxidative, anti-inflammatory, antiallergic, and antiapoptotic effects, we investigated the effects of our Si-based agent on mother-to-child transmission, with a focus on the rate of miscarriage. In pregnant mice fed a diet containing the Si-based agent, lipopolysaccharide-induced miscarriage due to mother-to-child transmission was reduced and inflammation and neutrophil infiltration in the placenta were suppressed. We also found that the Si-based agent suppressed IL-6 expression in the placenta and induced the expression of antioxidant and antiapoptotic genes, such as Hmox1 and Ptgs2. The observed anti-inflammatory effects of the Si-based agent suggest that it may be an effective preventative or therapeutic drug for miscarriage or threatened miscarriage during pregnancy by suppressing maternal inflammation caused by bacterial and viral infections.